A cryptography primer : secrets and promises - Klein, Philip N. (Cambridge : Cambridge University Press, 2014)
Cryptography has been employed in war and diplomacy from the time of Julius Caesar. In our Internet age, cryptography's most widespread application may be for commerce, from protecting the security of electronic transfers to guarding communication from industrial espionage. This accessible introduction for undergraduates explains the cryptographic protocols for achieving privacy of communication and the use of digital signatures for certifying the validity, integrity, and origin of a message, document, or program. Rather than offering a how-to on configuring web browsers and e-mail programs, the author provides a guide to the principles and elementary mathematics underlying modern cryptography, giving readers a look under the hood for security techniques and the reasons they are thought to be secure.
Machine generated contents note: 1. Introduction; 2. Modular arithmetic; 3. The addition cypher, an insecure block cypher; 4. Functions; 5. Probability theory; 6. Perfect secrecy and perfectly secure cryptosystems; 7. Number theory; 8. Euclid's algorithm; 9. Some uses of perfect secrecy; 10. Computational problems, easy and hard; 11. Modular exponentiation, modular logarithm, and one-way functions; 12. Diffie and Hellman's exponential-key-agreement protocol; 13. Computationally secure single-key cryptosystems; 14. Public-key cryptosystems and digital signatures.
Title from publisher's bibliographic system (viewed on 05 Oct 2015).
Keywords: Computer security; Data encryption (Computer science); Digital signatures; Telecommunication -- Safety measures